Implementation of Smart Government Through Digital Village Information System - Saadah, Mar Atun; Erida, Erida; Syeftiani, Try; Hendriyaldi, Hendriyaldi; Tialonawarmi, Feny; Tarigan, Steven Pradana; Rambe, Salwa Ayu Fadhillah (Jurnal Pengabdian UNDIKMA, 2024)
This service aims to increase the capacity of the village government in implementing smart governance with OpenSID while empowering the community as service users. This service employed the Participatory Action Research (PAR) method. The stages of activities carried out to achieve the goal were socialization of the urgency of SID in realizing Smart Village Governance. The activity was continued with training on the importance of SID for the Muaro Singoan Village Government. The team also provided assistance and training to the Village Government in managing the Village Information System through SID. Finally, socialization was carried out to the Muaro Singoan Village community regarding the understanding of the use of SID in serving the community. The service employed evaluation of attitude, knowledge, mentality, skills, partnership and follow-up that are conducted two weeks after the activity took place. This service resulted in changes in the knowledge, attitudes, mentality and skills of village communities and officials in organizing village governance with digital SID.